Trends in the Treatment of Adolescent Clavicle Fractures: Are We Listening to the Evidence?. (3rd February 2023) - Cole, Matthew W.; Collins, Lacee K.; Familia, McCayn M.; Skalak, Timothy J.; Lee, Olivia C.; Sherman, William F.
Abstract : Background: From 1999 to 2011, studies demonstrated an increasing trend toward surgical management of adolescent clavicle fractures. The purpose of this study was to examine more recent trends of surgical management of closed clavicle fractures in adolescent patients over the past decade. Methods: A retrospective cohort study was conducted using the PearlDiver database. Patients with clavicle fractures from 2011 to 2021 were identified and stratified by age, sex, and year of their fracture. Categorical variables were compared with a chi square test, and continuous variables were compared with the Welch t test or Mann-Whitney U test. Results: Overall, there was a significant increase in the percentage of patients surgically treated by open reduction and internal fixation from 2016 to 2021 compared with 2011 to 2015 (8.58% vs. 7.34%, P < 0.001). When stratified by age, both the 10 to 14-year group (3.80% vs. 3.10%, P < 0.001) and the 15 to 18-year group (15.41% vs. 12.84%, P < 0.001) demonstrated significant increases in the percentage of patients surgically treated. Conclusion: Despite increasing literature demonstrating high revision surgery rates for surgical treatment of adolescent clavicle fractures with no difference in functional outcomes, this study demonstrated a notable increase in the rate of surgical treatment of adolescent clavicle fractures from 2011 to 2021 in the United States.